PENERBIT USM SIGNS FOUR MOAs TO MARKET INTERNATIONAL EBOOKS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
FRANKFURT, GERMANY, 19 October 2015 – In the move to bring local written works from Malaysia, more so on studies and researches done by Universiti Sains Malaysia (USM) researchers to the international level, USM has signed four Memorandums of Agreement (MoA) with strategic partners to market the publications of Penerbit USM (USM Publisher) at the global level, signed at the Frankfurter Buchmesse (Frankfurt Book Fair) beginning from 14-18 October 2015.